Empowerment Public Based Nationality: Strengthening Indonesian National Values in Coastal Communities in Malaysia - Mustaid; Oman Hadiana; Tio Heriana; Hana Astria Nur; Rifqi Ahmad Fauzi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
This community service located on the Deep Coast of Kuala Lumpur Malaysia aims to provide education about nationality. The aim of taking nationality is because it is very strategic with the problems explained in the discussion and also seeing the large number of Indonesians who are on the Inner Coast of Kuala Lumpur, Malaysia. The method used is several stages which are carried out according to the procedure. Based on the problems obtained, the author created the title " Nationality-Based Community Empowerment; Strengthening Indonesian National Values in the Intellectual Community in Malaysia" Because Indonesian students and people have been in Malaysia for quite a long time so they really lack national insight. The content of the material presented is the importance of maintaining Indonesian national values, namely through programs implemented in the field. With this national-based strengthening, students and the community can certainly increase their understanding and enthusiasm to continue loving their homeland even though they are far from Indonesia